ANALISIS GANGGUAN JARINGAN TRANSMISI BERDASARKAN DFR DISTANCE RELAY DAN MENENTUKAN TITIK GANGGUAN MELALUI PERBANDINGAN ALAT PELACAK BERBASIS TWS DI GARDU INDUK SUNYARAGI - Annisa Azizzah; Dwi Sari Ida Aflaha (JURNAL ILMIAH NUSANTARA, 2025)
The reliability of electric power transmission is a crucial aspect of power system operation, as any disturbance can significantly impact the continuity of energy supply. Therefore, particularly in transmission networks, a protection system is required that not only responds to and minimizes disturbances promptly but is also capable of recording fault data for further analysis. This study presents a fault analysis of the transmission network based on data obtained from the Digital Fault Recorder (DFR) of distance relay to determine the fault characteristics and pinpoint the fault location, thereby accelerating fault handling. The analysis of fault characteristics is conducted using the fault signature method based on DFR of distance relay recordings, with fault location data compared to the results from the Travelling Wave System (TWS) to ensure accuracy. The results of this study successfully identify the type of fault, the involved phases, and the fault location with improved accuracy.